LIBRARY PROMOTION IN INCREASING VISITORS AT LIBRARY OF TANJUNGBALAI CITY - Yuma, A. Adnan Rasyidi; Dalimunthe, Muhammad; Naldo, Jufri (Academic Solution Publisher, 2023)
The research that has been carried out is entitled